Between Resilience and Radicalisation: Reassessing the Trajectory of Internally Displaced Populations in Cabo Delgado, Mozambique - Sidumo, Egna; Bertelsen, Bjørn Enge (Kronos, 2024)
Displacement is an endemic phenomenon that affects those uprooted, the communities that feel the impact of those arriving, governments, and the international agencies which are increasingly engaged in organising the displaced. The current war in the north of Mozambique, which has caused a massive displacement of people from 2017 onwards, may be related to a number of factors, including economic, social and even political. Although some actors and analysts include ethnicity as part of the causes, this has more often than not been analytically downplayed when grappling with the dynamics of, particularly, the groups that oppose the Mozambican government. This article analyses the dynamics of relationships between internally displaced people and host communities in Cabo Delgado, especially underlining, firstly, the resilience of communities in the face of extremist violence and, secondly, the distrust that typically shapes conflict. The latter dimension is aggravated by a historical past based on ethnic, political and social differences - cleavages that are accentuated and reproduced within the centres of displaced people and between these and host communities. We argue that factors such as poverty, hunger, lack of jobs or work opportunities, as well as poor access to arable land for family food production, exacerbate the relationship dynamics and create an environment conducive to the outbreak of small-scale conflicts that can, in the medium and long term, open spaces for radicalisation and more violence.